Soil Physical Properties of Oil Palm Plantations in Tidal Areas of Peatland - Herbin Dinto Simanullang; Dean Denaneer; Suratni Afrianti (The University of Lampung, 2024)
Oil palm (Elaeis guineensis Jacq) is a plant with a higher vegetable oil content than other oil-producing plants, so palm oil is widely used as the main raw material for processed vegetable oil. The increasingly limited land area and the larger land area in Indonesia so that the space for plantation companies to expand the land is increasingly limited, so that the expansion of oil palm plantations began to change from optimal land to suboptimal land. Soil physical properties are properties related to the shape or original condition of the soil. This study aims to determine the physical properties of soil (texture, porosity, moisture content, soil color, particle density, and bulk density) on peatlands in the tidal area of PT Sinar Gunung Sawit Raya. This research used survey method with descriptive analysis. The soil samples taken were peat soil in the tidal area with purposive random sampling method at a depth of 30 cm. This research was conducted in November 2023 and continued in the laboratory for testing each soil physical properties. The results of the research on soil physical properties at PT Sinar Gunung Sawit Raya on peatlands in tidal areas show that the soil texture is loamy sand, soil porosity is good, moisture content is relatively normal, soil color looks relatively dark, particle density is still low and bulk density value shows low. Keywords: Loamy sand, Oil palm, Peat soil, Soil color, Soil texture.